The Impact of Pallidal and Subthalamic Deep Brain Stimulation on Urologic Function in Parkinson's Disease. Issue 7 (12th May 2016) - Mock, Stephen; Osborn, David J.; Brown, Elizabeth T.; Stuart Reynolds, W.; Turchan, Maxim; Pallavaram, Srivatsan; Rodriguez, William; Dmochowski, Roger; Tolleson, Christopher M.
Abstract : Objective: Deep Brain Stimulation (DBS) is an established adjunctive surgical intervention for treating Parkinson's disease (PD) motor symptoms. Both surgical targets, the globus pallidus interna (GPi) and subthalamic nucleus (STN), appear equally beneficial when treating motor symptoms but effects on nonmotor symptoms are not clear. Lower urinary tract symptoms (LUTS) are a common PD complaint. Given prior data in STN‐DBS, we aimed to further explore potential benefits in LUTS in both targets. Methods: We performed a prospective, nonblinded clinical trial evaluating LUTS in PD patients in both targets pre and post DBS using validated urologic surveys. Participants were already slated for DBS and target selection predetermined before study entry. LUTS was evaluated using: the American Urological Association (AUA‐SI), Quality of Life score (QOL), Overactive Bladder 8 Questionnaire (OAB‐q), and Sexual Health Inventory for Men (SHIM). Results: Of 33 participants, 20 underwent STN DBS and 13 had GPi DBS. Patients demonstrated moderate baseline LUTS. The urologic QOL score significantly improved post DBS (3.24 ± 1.77vs. 2.52 ± 1.30; p = 0.03). Analyzed by target, only the STN showed significant change in QOL (3.20 ± 1.61 vs 2.25 ± 1.33; p = 0.04). There were no other significant differences in urologic scores post DBS noted in either target. Conclusion: In PD patients with moderate LUTS, there were notable improvements in QOL for LUTS post DBS in the total sample and STN target. There may be differences in DBS effects on LUTS between targets but this will require further larger, blinded studies.